2005
DOI: 10.1002/chin.200511211
|View full text |Cite
|
Sign up to set email alerts
|

Thymidylate Synthase Polymorphism and Microsatellite Instability: Association in Colorectal Cancer

Abstract: For Abstract see ChemInform Abstract in Full Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2010
2010
2010
2010

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 1 publication
2
0
0
Order By: Relevance
“…69 Expression of the TS gene has also been shown to be dependent on MSI. For example, the present study, which is in agreement with Ricciardiello et al, 24 Calascibetta et al, 70 and Jensen et al, 71 shows that cancers with MSI have higher levels of TS protein than MSS tumours. To the best of our knowledge, the present study showed for the first time that TS mRNA levels are significantly higher in MSI tumours than in MSS tumours.…”
Section: Table 3: Intratumoural Thymidylate Synthase (Ts) Scores (Prosupporting
confidence: 93%
See 1 more Smart Citation
“…69 Expression of the TS gene has also been shown to be dependent on MSI. For example, the present study, which is in agreement with Ricciardiello et al, 24 Calascibetta et al, 70 and Jensen et al, 71 shows that cancers with MSI have higher levels of TS protein than MSS tumours. To the best of our knowledge, the present study showed for the first time that TS mRNA levels are significantly higher in MSI tumours than in MSS tumours.…”
Section: Table 3: Intratumoural Thymidylate Synthase (Ts) Scores (Prosupporting
confidence: 93%
“…To the best of our knowledge, the present study showed for the first time that TS mRNA levels are significantly higher in MSI tumours than in MSS tumours. These findings for TS mRNA, however, were made using a small sample size and the results are in contrast with the findings of Calascibetta et al 70 This increase in TS gene expression could not be explained by altered TS genotype, although all MSI tumours were heterozygous or homozygous for the SNP, which is in agreement with previously published studies. 72 All MSI tumours had a reaction pattern of 2 or 3, and a correlation between high TS protein levels and a reaction pattern of 3 (diffuse strong staining of the carcinoma cells) was seen; Lindebjerg et al 47 previously reported a correlation between genotype (3R/3R) and staining pattern (staining pattern 3).…”
Section: Table 3: Intratumoural Thymidylate Synthase (Ts) Scores (Prosupporting
confidence: 84%